PERSEPSI WARGA BELAJAR DALAM KEGIATAN PEMBELAJARAN PROGRAM PENDIDIKAN KESETARAAN DI SATUAN PENDIDIKAN NON FORMAL (SPNF) SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Khotimah, Khusnul; Jas, Jaspar; Sumardi, Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the perception of learning citizens in learning activities. So that the formulation of the problem of this research is whether the perception of citizens learning in learning activities in equality education programs SPNF SKB Pekanbaru City is quite good?. The purpose of this study is for the perception of citizens learning in the learning activities of equality education programs in the SPNF SKB Pekanbaru City. The population in this study were 59 people learning. Then the sample of this study were 37 people and 20 people learning for the sample trial with a critical level of 10%, the sample used was simple random sampling. The data collection instrument was a questionnaire with 40 statements and after the trial remained only 47 valid statements to be made as research instruments. Data analysis through quantitative descriptive analysis. The weight of each answer for Very Good (SB) with a score of 5, Good (B) with a score of 4, Fairly Good (CB) with a score of 3, Poorly Good (KB) with a score of 2, Not Good (TB) with a score of 1. From the findings of the study of the three indicators it can be concluded that the indicator is classified as good. This is evidenced by the presentation of the recapitulation of the perceptions of learning citizens in the learning activities of the equality education program in the SPNF SKB Pekanbaru City as a whole indicator; (1) accepting those who stated (SB + B) 73%, (2) understood those who stated (SB + B) 73%, and (3) rated those who stated (SB + B) 71%. the perception of citizens learning in the learning activities of the equality education program in the SPNF SKB Pekanbaru City is quite good. This means that citizens learn to have a good view of the tutor when presenting learning materials and facilities at SKB. .Key Words: Perception, Perception of Citizens Learning